Developing a Bilingual Website for Jodipan Kampung Warna Warni - Syani, Syafika Shalshabilla; Lestari, Pritantina Yuni; Hoesny, Mariana Ulfah (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2024)
Jodipan Kampung Warna-Warni is a popular tourist destination in Malang, Indonesia, known for the uniqueness and beauty of its colorful buildings. This research focuses on developing a bilingual website for Jodipan Kampung Warna-Warni (KWWJ). The main objective of this research is to develop a bilingual website for Jodipan Kampung Warna-Warni to both local and international tourist through effective digital media. The website also utilizes both Indonesian and English languages. The research employed the Design and Development and Development Research (DDR) method, which includes five steps: analysis, design, development, implementation, and evaluation. Data were gathered through documentation, observation, interviews, and questionnaires. The product was validated by language and IT expert to ensure its quality.  The evaluation results indicate that the bilingual website, designed effectively for informational and promotional purposes, meets the standards for high-quality, well-designed site. This conclusion is based on positive feedback collected through questionnaires distributed to both local and international potential customers, showing that the website met the criteria for a well-designed platform suitable for publication. Users appreciated the ease of navigation, clarity of information, and interactive features. Consequently, this bilingual website is expected to serve as a model for other tourist destinations in leveraging digital technology for more effective promotion.